MEANINGFUL PARTICIPATION OF YOUNG PEOPLE IN POLICIES AND PROGRAMMES TO ENSURE ENHANCED ACCESS TO SEXUAL REPRODUCTIVE HEALTH (SRH) INFORMATION AND SERVICES IN INDIA (Proceedings of the International Conference on Public Health, 2025)
India is home to an estimated 370 million young people, the largest in the world (Census 2011, Population Projections for India and States, 2011 – 2036) making Sexual and reproductive health (SRH) a critical component for ensuring health and well-being of young people thereby contributing to their holistic development. Given the current policy environment in the country, there are only two government programmes namely Rashtriya Kishor Swasthya Karyakram (focuses on adolescents, below age of 18) and Mission Parivar Vikas (focuses on married couples, both over and under the age of 18) with provisions for ensuring access to information and services pertaining to SRH. These programs have an obvious blind spot, with unmarried young people over the age of 18 left out from the service provision. Therefore, the challenge to address the diverse SRH needs of young people still persists. In order to comprehend the obstacles involved in the SRH service delivery for young people, a qualitative assessment was conducted through 90 key informant interviews with health service providers and RKSK programme implementers identified using randomised sampling technique across 10 states. The qualitative data was codified and analysed to highlight the key findings based on the narratives and anthology of the respondent’s feedback. The qualitative assessment led by young people highlighted the lack of awareness, staggered access to information among adolescents about the SRH services, low footfall of adolescents at Adolescent Friendly Health Clinics (AFHCs), incompetent and judgemental service delivery by the providers as key findings behind high unmet need of SRH services among young people. Using this data, youth champions across four states supported the government health functionaries in anchoring 6 Adolescent Health and Wellness Days (AHWDs) influencing about 2.5 lac people. This model of ecosystem approach of centering young people’s experiences to strengthen, design and deliver programmes ensures sustainability and effectiveness of SRH initiatives
Keywords: Sexual Reproductive Health Rights; Young people; India; Adolescent health; SRH programmes